URGENSI PERNCATATAN PERKAWINAN PERSPEKTIF HUKUM ISLAM - Chaula Luthfia (Sahaja: Journal Sharia and Humanities, 2022)
Marriage registration in Islamic family law is not regulated, marriage is valid if it meets the requirements and pillars. Along with the development of increasingly modern times, marriage is not only carried out between regions anymore. In the past, it was sufficient for the announcement of the context with witnesses and walimah al `urusy, but this form of announcement for the present context is no longer relevant. This research is a type of library research, the author uses a normative and philosophical approach. The results of this study found that in the early days of Islam there was a tradition of I'lan an-nikah (announcing a marriage in the midst of the local community). One form of I'lan an-nikah is walimah al-urs (reception/wedding party), the call has the intention of announcing to the public that a marriage has occurred and preventing adultery prejudice. There is a recommendation to record non-cash transactions in Qs. Al Baqarah (2) verse 282, where the legal illat is to strengthen testimony and avoid doubt. It is explained in the Qur'an letter an-Nisa 'verse 21 that marriage is not an ordinary muamalah but a very strong agreement ? ???????. Therefore, marriages that have a special position, namely a very strong agreement, so noble, majestic, and sacred are even more important to be recorded. Announcements relevant to the current context appear in written form in the form of a marriage certificate. So that the marriage certificate is a form of community recognition and guarantor of rights in the present. In other words, the context of public announcements as a means of recognizing and guaranteeing rights is for communal communities who are accustomed to oral communication.